2023
DOI: 10.3389/fncel.2023.1131683
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of heat shock proteins HSP70 in the mechanisms of endogenous neuroprotection: the prospect of using HSP70 modulators

Abstract: This analytical review summarizes literature data and our own research on HSP70-dependent mechanisms of neuroprotection and discusses potential pharmacological agents that can influence HSP70 expression to improve neurological outcomes and effective therapy. The authors formed a systemic concepts of the role of HSP70-dependent mechanisms of endogenous neuroprotection aimed at stopping the formation of mitochondrial dysfunction, activation of apoptosis, desensitization of estrogen receptors, reduction of oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 170 publications
0
9
0
Order By: Relevance
“…We found that HSP70 "prolongs" the action of HIF-1a, and also independently maintains the expression of NAD-MDH-mx, thereby maintaining the activity of the compensatory mechanism of ATP production-the malate-aspartate shuttle mechanism-for a long time [58]. Our works have shown that Angiolin can activate the malate-aspartate shuttle mechanism in the myocardium during ischemia [56].…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…We found that HSP70 "prolongs" the action of HIF-1a, and also independently maintains the expression of NAD-MDH-mx, thereby maintaining the activity of the compensatory mechanism of ATP production-the malate-aspartate shuttle mechanism-for a long time [58]. Our works have shown that Angiolin can activate the malate-aspartate shuttle mechanism in the myocardium during ischemia [56].…”
Section: Discussionmentioning
confidence: 50%
“…To date, it is known that the mechanisms of the protective action of HSP70 are realized due to the restoration of the correct tertiary structure of damaged proteins, as well as in the formation and dissociation of protein complexes. Our studies revealed the positive role of HSP70 aimed at reducing the formation of mitochondrial dysfunction in neurons of the sensorimotor cortex and hippocampus in cerebral ischemia [56]. The therapeutic effect of the investigated pharmacological agents after PH can be explained as follows.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Nitrosative stress also leads to heat shock protein 70 (HSP70) deficiency in the cell by depriving the glutathione linked of the thiol-disulphide system. Cytotoxic forms of NO not only lead to the modification (reversible and irreversible) of macromolecules, including HSP70 itself, but also reduce the expression activity of the genes encoding its synthesis [42,43]. Role of NO derivatives in suppressing gene activity and reducing levels of various transcription factors demonstrated [44].…”
Section: Neonatal Posthypoxic Myocardial Hypertrophy Factors Of Gene ...mentioning
confidence: 99%
“…Cu has been found to be repressed in neurons with evidence of apoptosis, while Zn-SOD is known to bind and facilitate the production of significant amounts of endogenous peroxynitrite (ONOO − ) [160][161][162]. Low concentrations of • NO donors have been shown to inhibit neuroapoptosis induced by growth factor deprivation or TNF-α addition, potentially through the activation of the heat shock protein HSP70 or the inhibition of caspase-3 [163,164]. Dinitrosyl iron complexes (DNICs) at concentrations ranging from 5 to 10 µM are believed to suppress IL-1β-induced neuroapoptosis by promoting • NO synthesis.…”
Section: Apoptosis and • Nomentioning
confidence: 99%